Spatiotemporal Evolution Mechanism and Dynamic Simulation of the Urban Resilience System in the Chengdu–Chongqing Economic Circle - Huang, Huiqin; Yang, Xia (Sustainability, 2025)
The system subject, resilience capacity, and factor endowment are the core elements of resilient city construction. A rational assessment of urban resilience is crucial for transforming the urban governance paradigm. This study develops an analytical framework for resilient city system (RCS) grounded in the conceptual connotation and constituent elements of urban resilience. Using the strategically significant Chengdu–Chongqing Economic Circle (CCEC) as a case study, an urban resilience (UR) index system was proposed, encompassing economics, society, ecology, infrastructure, and organizational management. A panel dataset of urban resilience indicators was compiled using official data from national and local urban statistical yearbooks spanning 2012 to 2022. By analyzing the spatiotemporal evolution patterns of the CCEC, this study revealed the dominant factors influencing these patterns and dynamically simulated the urban resilience of the CCEC over the next 16 years. The findings indicate the following: (1) During 2012–2022, the urban resilience of the CCEC transitioned from a “single-core” model centered on Chongqing to a “dual-core” model featuring both Chongqing and Chengdu. The overall level of urban resilience in the study area exhibited an upward trend, characterized by a spatially divergent pattern with two prominent wings and a concave center. (2) Economic factors, social factors, and facility factors were identified as the dominant factors affecting urban resilience in the CCEC. (3) Projections for 2025–2035 suggest that the urban resilience level of the CCEC will continue to increase steadily at a moderate pace. These results provide valuable theoretical references for advancing the high-quality development of the CCEC and fostering a development pattern characterized by “two-wing drive and whole-area synergy”.